2022
DOI: 10.1186/s40545-022-00455-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental COVID-19 vaccination hesitancy among parents of children aged 5–18 years in Thailand: a cross-sectional survey study

Abstract: Background To promote an acceptance rate of COVID-19 immunization among Thai children, concerns about parental vaccination hesitancy should be urgently studied. This study aimed to examine the parental COVID-19 vaccination hesitancy (PVh) level and influencing factors among Thai parents of children 5–18 years of age. Methods This cross-sectional survey was conducted in Thailand during May and June of 2022. The Google forms for data collection were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
2
2
Order By: Relevance
“…The acceptance rates of Pfizer-BioNTech for children aged 12-18 and under 5-11 in our study were higher than the rate mentioned above. Another study, recruiting participants via social network platforms, reported that 42% of respondents accepted the COVID-19 vaccine [16] , which is much lower than our study's finding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The acceptance rates of Pfizer-BioNTech for children aged 12-18 and under 5-11 in our study were higher than the rate mentioned above. Another study, recruiting participants via social network platforms, reported that 42% of respondents accepted the COVID-19 vaccine [16] , which is much lower than our study's finding.…”
Section: Discussioncontrasting
confidence: 99%
“…This study examined parents’ acceptance of the Pfizer-BioNTech and the Sinopharm COVID-19 vaccine for children aged 5-18 and its association with HBM domains. Compared to two previous studies [16] , [17] , this was the first nation-wide study with probability sampling. The findings showed that 90% and 36% of the respondents accepted the Pfizer-BioNTech and the Sinopharm COVID-19 vaccine, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The lower rate of intention to have their children vaccinated was associated with being uncertain about the safety and efficacy of the vaccine [ 20 , 22 , 31 ]. We found that parents’ intention to vaccinate themselves and their intention to vaccinate their children were not significantly associated in this study, although this association was significant in other studies [ 20 , 21 , 22 , 37 , 38 ]. The different intention rates may be due to differences in the age groups being studied [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 91%
“…This is despite 96.7% of the parents having been vaccinated, although statistical analysis showed that having completed the initial vaccination (two-dose) is a protective factor. Negative attitudes toward COVID-19 and COVID-19 vaccines, a history of refusing COVID-19 vaccination for themselves and other vaccinations for children are associated with a higher risk of vaccine hesitancy [19]. This may limit the vaccine uptake in the recently launched vaccination drive for children, causing wastage of the vaccines allocated for the program.…”
Section: Vaccine Hesitancymentioning
confidence: 99%